P-200 Quality improvement in action – improving care for patients admitted to hospital in an emergency. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Grant, Julia; Murray, Karen; Olivant, Valerie; Hyde, Lizzie; Russ, Kate
Abstract : Background: University Hospitals Leicester (UHL) joined a quality improvement collaborative (ECLHIP) to improve care for patients who maybe in their last three months of life who attend or are admitted to hospital in an emergency. Hospitals are an important provider of care for this group. UHL is one of the largest Trusts in the English NHS, caring for over 2000 patients in their last days of life each year. An emergency admission may indicate underlying clinical decline. Quality of care varies and there may be unwanted inpatient stays and/or treatments contributing to overall experience. Method: The collaborative begins with diagnosis (activity data, qualitative casefile review, patient experience walkthrough, review of reports and plans). A driver diagram illustrates the 'theory of change' based on findings to plan improvements. The model for improvement provides the framework for engaged frontline clinicians to conduct tests of change. The approach includes informative evaluation, patient and relative experience and planning for sustainability. Results: 62% (n=1991) emergency, adult patients who died in UHL had an outpatient appointment, emergency admission, attendance and/or planned admission in the 90 days preceding their final admission. Casefile review: 7/10 patients had likely missed opportunities to plan ahead. During the final admission, uncertain recovery and/or dying was recognised but this was often late and/or did not translate into desired action. A survey of A and E staff indicated gaps in knowledge on how to access SPC (24% confident) and communication around patients who are dying/providing bereavement support (65% confident). Conclusions: Tests of changes need to be small enough to try within existing workloads. The focus for July to Sept 2018 (cycles: 1 clinician, 10 patients informed by patient/relative experience) is: improved handover and future care planning on discharge (acute frailty) earlier recognition, communication alongside improving knowledge/access to SPC (A&E).